Pengaruh penggunaan media pembelajaran multimedia interaktif terhadap hasil belajar siswa kelas V pada materi teks eksplanasi - Syarah, May; Indriani, Lina; Oktari, Senny Widia (Didaktika Dwija Indria, 2025)
The use of instructional media is a fundamental aspect of the teaching and learning process, as it facilitates students’ comprehension of lesson content. This study aims to examine the effect of interactive multimedia learning media on the academic achievement of fifth-grade students, specifically in Bahasa Indonesia, focusing on explanatory texts. The research employed a quasi-experimental method with a one-group pretest-posttest design to investigate the causal relationship between the use of interactive multimedia and student learning outcomes. The instruments used were pretests and posttests administered to fifth-grade students at SDS Al-Washliyah 15 Medan Timur. Normality testing using the Shapiro-Wilk test yielded a significance value of 0.734 for the pretest and 0.023 for the posttest, indicating that the data were not normally distributed. Consequently, the Wilcoxon Signed Ranks Test was employed and produced a significance value of 0.000 (< 0.05), confirming a significant difference in learning outcomes before and after the intervention. The effectiveness analysis using the N-Gain Score revealed an average gain of 0.65, categorized as “moderate,” and a learning mastery level of 88%, classified as “very good.” These results indicate that the use of interactive multimedia learning media has a significant positive impact on students' performance in understanding explanatory texts.